(untitled) (Journal of the College of Basic Education, 2026)
Performance is linked to the individual’s body, which falls within the social framework. It constitutes that social system. Accordingly, all celebrations held across civilizations rely on bodily movements and connotations as a social subject. The body, in its biological makeup, is based on sensory and motor abilities. It is the source of meaning, and these motor abilities are focused on intertwining and interweaving a set of activities organized by the actor through thought and memory. These activities rely on mentality, harmony, and this idea is translated into the form of the theatrical performance, based on the visualization of mental symbols and vocabulary that stimulate the recipient’s mind. The body, in its social sense, carries signs and connotations through the actor’s performance, whether kinetic or gestural. Consequently, it expresses semantic meanings that are harmonious, compatible, and consistent, providing concepts through mental perception. This is reflected in the actor’s role on stage through his craftsmanship. These symbols accumulate in the form of mental images, and these images control the actor’s behavior in an intentional way through performance interference. This is positively reflected in the process of forming and constructing the theatrical image and translates his thinking and feeling into understandable and tangible molds for the recipient through the word, which is a spoken or unspoken meaning. The research question was launched as follows: Is there a performance interference between the body and the word in the short performances of the Unexpected Kinetic Theater, the play Da’balak - as a model?